2020
DOI: 10.3961/jpmph.19.218
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Frequency of Eating Non-home-prepared Meals and Women Infertility in the United States

Abstract: The purpose of this study was to determine whether eating non-home-prepared meals (NHPM), including fast food, readyto-eat foods, and frozen foods, was associated with self-reported infertility in the United States women. Methods: Data on diet and infertility from women aged 20-49 years who participated in the 2013-2014 and 2015-2016 National Health and Nutrition Examination Surveys were analyzed (n=2143). Dietary information, including the number and types of NHPM consumed, was obtained from a self-reported q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(43 reference statements)
0
2
0
1
Order By: Relevance
“…Dieta ocidental e consumo alimentar fora de casa Pelo seu elevado teor em gordura, a ingestão de refeições fora de casa, nomeadamente de fast-food, poderá estar associada à infertilidade (61). Uma coorte com cerca de 5 600 mulheres verificou uma tendência significativa para a diminuição da fertilidade e aumento do tempo necessário para alcançar a gravidez com o aumento da ingestão de fast-food na preconceção (p para a tendência = 0,001, em ambos os casos) (62).…”
Section: Papel Dos Padrões Alimentares Na Fertilidade Femininaunclassified
“…Dieta ocidental e consumo alimentar fora de casa Pelo seu elevado teor em gordura, a ingestão de refeições fora de casa, nomeadamente de fast-food, poderá estar associada à infertilidade (61). Uma coorte com cerca de 5 600 mulheres verificou uma tendência significativa para a diminuição da fertilidade e aumento do tempo necessário para alcançar a gravidez com o aumento da ingestão de fast-food na preconceção (p para a tendência = 0,001, em ambos os casos) (62).…”
Section: Papel Dos Padrões Alimentares Na Fertilidade Femininaunclassified
“…Additionally, a large-scale birth cohort study in Japan demonstrated that the consumption of ready-made and frozen meals during pregnancy may increase the risk of stillbirth [19]. Another study conducted in the United States suggested that the consumption of meals not prepared at home may contribute to the risk of infertility in women [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that ready-made meal consumption is associated with an increased risk of overweight and obesity [3]; however, others have reported no such association [4]. The effects of consumption of processed foods during pregnancy on pregnancy outcomes have been largely unexplored; the evidence is confined to one study that suggests that consumption of meals not prepared at home may contribute to the risk of infertility [5]. The prospective birth cohort in Osaka, Japan, showed that the average intake of coffee in pregnant women is 0.14 cups/day [6].…”
Section: Introductionmentioning
confidence: 99%